Ascent (The Invasion Chronicles-Book Three): A Science Fiction Thriller - Morgan, Rice (Lukeman Literary, 2018)
"TRANSMISSION is riveting, unexpected, and firmly rooted in strong psychological profiles backed with thriller and sci-fi elements: what more could readers wish for? (Just the quick publication of Book Two, Arrival.)" --Midwest Book Review From #1 worldwide bestselling fantasy author Morgan Rice comes book #3 in a long-anticipated science fiction series. With planet Earth destroyed, what will become of 13 year old Kevin and Chloe in the mother ship? Will the aliens enslave them? What do they want? Is there any hope of escape? And will Kevin and Chloe ever return to Earth again? "Action-packed .... Rice's writing is solid and the premise intriguing." -Publishers Weekly, re A Quest of Heroes "A superior fantasy... A recommended winner for any who enjoy epic fantasy writing fueled by powerful, believable young adult protagonists." -Midwest Book Review, re Rise of the Dragons "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as THE INHERITANCE CYCLE by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." -The Wanderer, A Literary Journal (regarding Rise of the Dragons) Book #4 in the series will be available soon. Also available are Morgan Rice's many series in the fantasy genre, including A QUEST OF HEROES (BOOK #1 IN THE SORCERER'S RING), a free download with over 1,300 five star reviews!
Keywords: Young Adult, New Adult